(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): Technology transition (TT) is innovation macro process where new technologies replace the old ones. Dynamic of technology transition distinguishes raise, stagnation and fall of technology. Research question is how it is possible to describe technology transition qualitatively. Purpose: Research work is to develop a universal mathematical model that will describe various technology transitions by means of parameter change. Method: The phenomenon was analysed and exogenous and endogenous variables have been identified along with their causal relations, including mathematical logic and induction. The model was verified with specific data. Results: Verification on actual data has shown that developed mathematical model adequately describes three technology transition states: Raise, stagnation and fall of technology. Organisation: Model is of generic nature but is as well applicable for technology transfer in organisation, provided the adequate data are available in the organisations. Society: Model is of generic nature and enables the technology transition modeling. Originality: Research is original. We could not find any mathematical model that would describe technology transitions. Limitations/Future Research: Two sigmoid functions have been used for parameter identification for personal car technology transition and passenger air transport transition in Slovenia. Further research is possible in model verification with other sigmoid functions and data for other countries/regions.